2015
DOI: 10.1007/s10803-015-2492-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Visual–Tactile Interactions over Time and Space in Adults with Autism

Abstract: It has been suggested that the sensory symptoms which affect many people with autism spectrum conditions (ASC) may be related to alterations in multisensory processing. Typically, the likelihood of interactions between the senses increases when information is temporally and spatially coincident. We explored visual-tactile interactions in adults with ASC for the first time in two experiments using low-level stimuli. Both participants with ASC and matched neurotypical controls only produced crossmodal interactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(29 citation statements)
references
References 55 publications
2
24
3
Order By: Relevance
“…Considering this issue of spatial discrepancy between the cues, it is interesting that participants with ASC and NT adopted a similar strategy in the present study. In a previous study, visual-tactile interactions were observed at a greater spatial discrepancy in ASC (Poole et al, 2015) which could reflect an extended representation of peripersonal space in ASC and suggest that participants with ASC would be more likely to integrate spatially discrepant cues.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Considering this issue of spatial discrepancy between the cues, it is interesting that participants with ASC and NT adopted a similar strategy in the present study. In a previous study, visual-tactile interactions were observed at a greater spatial discrepancy in ASC (Poole et al, 2015) which could reflect an extended representation of peripersonal space in ASC and suggest that participants with ASC would be more likely to integrate spatially discrepant cues.…”
Section: Discussionmentioning
confidence: 70%
“…This was motivated primarily by two previous findings in the literature: firstly, NT participants have been shown consistently to integrate visual-haptic information in an optimal manner (Ernst and Banks, 2002;Gori et al, 2008). Secondly, it has been proposed that individuals with ASC may not integrate reliability information in an optimal manner (Lawson et al, 2014;Pellicano and Burr, 2012) and aspects of multisensory processing are disrupted in this group (Poole et al, 2015;Russo et al, 2010). .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As visual-auditory temporal acuity is believed to be reduced in ASC, it is interesting that in the present study the effect size was smallest (d = 0.02) for the between group comparison of visual-auditory JNDs. This suggests that temporal acuity is comparable to NTs in some adults with ASC (see de Boer-Schellekens et al 2013; Poole et al 2015 for similar recent findings). As multisensory temporal acuity typically matures across development (Hillock et al 2011; Hillock-Dunn and Wallace 2012) there may be a delay in the maturation of this processing in ASC which may have ‘caught up’ with NT performance by adulthood (see Foxe et al 2015; Taylor et al 2010, for evidence of maturation of visual-auditory speech processing in adolescents with ASC).…”
Section: Discussionmentioning
confidence: 62%
“…In the tactile-visual condition participant JNDs were a significant predictor of self-reported sensory reactivity, such that those with reduced tactile-visual temporal acuity reported greater sensory reactivity. Reduced tactile-visual temporal acuity could lead to atypical experiences of touch which could impact on higher level processes such as the experience, and use, of inter-personal touch (Poole et al 2015) and in planning movements, particularly involving objects (Gowen and Hamilton 2013). Furthermore, participants who required a greater auditory lead to perceive visual-auditory stimuli as simultaneous reported more atypical sensory reactivity.…”
Section: Discussionmentioning
confidence: 99%